Evaluation of Karnofsky Performance Scale as a Postsurgical Prognosis Criteria in Chronic Subdural Hematoma Cases: Discordance Between Clinical and Radiological Outcomes: Karnofsky Scoring for Subdural Hematoma - Asan, Ziya; Eroglu, Sercan; Koysuren, Aydan; Durmaz, Sezai (International Clinical Neuroscience Journal, 2023)
Background: Chronic subdural hematoma (CSDH) may cause neurological deficits as well as adverse effects on the patient’s general health status. Although CSDH cases are diagnosed in the advanced age group with a very high rate, clinical findings may not be related only to CSDH. The aim should be related to clinical recovery rather than radiological recovery for these cases. We aimed to evaluate Karnofsky’s score as a measurement criterion of postoperative clinical outcomes in patients with CSDH. Methods: Cases operated for the diagnosis of CSDH were defined retrospectively. The cases that had been operated with this diagnosis were identified by examining the institution database records. Karnofsky scores equivalent to clinical status were performed by examining patient files. Karnofsky scoring before the symptomatic period was determined and compared with the Karnofsky score belonging to the late postoperative period. The clinical and radiological findings of the preoperative and postoperative periods were compared. Independent samples t test was used to reveal the difference between the two groups. Results: Data of 184 cases were evaluated. Seventy-three cases were operated on the left, 51 cases on the right, and 60 cases bilaterally with the diagnosis of CSDH. Burrhole exploration was performed in 119 cases, and a craniotomy was performed in 65 cases. Although a significant decrease in hematoma thickness was detected radiologically in cases operated with the craniotomy method, a more significant improvement was observed in Karnofsky’s score in cases operated with the burrhole method. In younger patients, improvement in Karnofsky’s score was significantly higher. Conclusion: The main aim should be to improve clinical status rather than radiological improvement in the treatment of CSDH cases. In the surgical treatment of these cases, it is possible to encounter a high rate of complications depending on age. It is possible to evaluate the postoperative status rationally with Karnofsky scoring. According to the preoperative Karnofsky scoring, deciding on the surgical technique may help reduce complications.